The mobile phone as an argument for good governance in sub-Saharan Africa. Issue 4 (12th October 2018) - Asongu, Simplice; le Roux, Sara; Nwachukwu, Jacinta C.; Pyke, Chris
Abstract : Purpose: The purpose of this paper is to present theoretical and empirical arguments for the role of mobile telephony in promoting good governance in 47 sub-Saharan African countries for the period 2000–2012. Design/methodology/approach: The empirical inquiry uses an endogeneity-robust GMM approach with forward orthogonal deviations to analyze the linkage between mobile phone usage and the variation in three broad governance categories – political, economic and institutional. Findings: Three key findings are established: first, in terms of individual governance indicators, mobile phones consistently stimulated good governance by the same magnitude, with the exception of the effect on the regulation component of economic governance. Second, when indicators are combined, the effect of mobile phones on general governance is three times higher than that on the institutional governance category. Third, countries with lower levels of governance indicators are catching-up with their counterparts with more advanced dynamics. Originality/value: The study makes both theoretical and empirical contributions by highlighting the importance of various combinations of governance indicators and their responsiveness to mobile phone usage.